2019
DOI: 10.1111/bph.14580
|View full text |Cite
|
Sign up to set email alerts
|

Spinal α2‐adrenoceptors and neuropathic pain modulation; therapeutic target

Abstract: Neuropathic pain can arise from disease or damage to the nervous system. The most common symptoms of neuropathic pain include spontaneous pain, allodynia, and hyperalgesia. There is still limited knowledge about the factors that initiate and maintain neuropathic pain. However, ample evidence has proved the antinociceptive role of spinal α‐adrenoceptors following nerve injury. It is well‐documented that https://www.sciencedirect.com/topics/neuroscience/norepinephrine descending pathways from supraspinal loci ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 149 publications
(197 reference statements)
0
31
0
Order By: Relevance
“…We have recently shown that in paclitaxel-induced CIPN there is an increased activation of serotoninergic RVM neurons (Costa-Pereira et al, 2019). Since the RVM targets the LC and this connection is relevant for descending noradrenergic pain modulation (Sim and Joseph, 1992;Bahari and Meftahi, 2019) it is possible that the activation of RVM neurons recently reported in the paclitaxel-induced CIPN model (Costa-Pereira et al, 2019) is a trigger of increased recruitment of noradrenergic descending modulation during CIPN.…”
Section: Discussionmentioning
confidence: 92%
“…We have recently shown that in paclitaxel-induced CIPN there is an increased activation of serotoninergic RVM neurons (Costa-Pereira et al, 2019). Since the RVM targets the LC and this connection is relevant for descending noradrenergic pain modulation (Sim and Joseph, 1992;Bahari and Meftahi, 2019) it is possible that the activation of RVM neurons recently reported in the paclitaxel-induced CIPN model (Costa-Pereira et al, 2019) is a trigger of increased recruitment of noradrenergic descending modulation during CIPN.…”
Section: Discussionmentioning
confidence: 92%
“…So, to the best of our knowledge, this is the first time that such study investigates the mechanism of anti-nociceptive effects of crocin. It is well documented that αadrenoceptors are an important therapeutic target for pain [5]. In the spinal cord level, descending adrenergic projection from the brain stem nuclei to the spinal cord can suppress pain perception [34].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of neuropathic pain is far from clear. The α-adrenoceptors have critical contribution in the process of pain information [5]. Nakai and colleagues revealed that intrathecal injection of guanfacine (an α2Aadrenoceptors agonist) and nitrobiphenyline (an α2C-adrenoceptor agonist) increased mechanical thresholds in a rat model of trigeminal neuropathic pain [6].…”
Section: Introductionmentioning
confidence: 99%
“…130 Moreover, activation of the noradrenergic descending pathway inhibits the activities of the spinal cord nociceptive receptors, such as α 2 -adrenoceptors. 131,132 It is documented that intrathecal melatonin alleviates mechanical allodynia response in the formalin test, which is mediated through α 1 -adrenoceptors, α 2 -adrenoceptors, muscarinic, and nicotinic receptors in the spinal cord. 60 In addition, agomelatine exhibits anti-allodynia through noradrenergic neurotransmission mediated by α 2 -adrenoceptors and β 2 -adrenoceptors.…”
Section: Adrenergic Receptorsmentioning
confidence: 99%